2005
DOI: 10.1152/ajpgi.00064.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in intestinal apolipoprotein A-IV and its relation to food intake and corticosterone in rats

Abstract: To further investigate the role of intestinal aplipoprotein A-IV (apo A-IV) in the management of daily food intake, we examined the diurnal patterns in apo A-IV gene and protein expression in freely feeding (FF) and food-restricted (FR; food provided 4 h daily for 4 wk) rats that were killed at 3-h intervals throughout the 24-h diurnal cycle. In FF rats, the intestinal apo A-IV mRNA and protein levels showed a circadian rhythm concomitant with the feeding pettern. The daily pattern of fluctuation of apo A-IV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Lipids-ApoAIV expression shows diurnal variations (13,38,39). Consistent with these studies, apoAIV mRNA levels were low in the daytime and high at night in wild-type mice (Fig.…”
Section: Effect Of Apoaiv Deficiency On Diurnal Variations In Plasmasupporting
confidence: 86%
See 1 more Smart Citation
“…Lipids-ApoAIV expression shows diurnal variations (13,38,39). Consistent with these studies, apoAIV mRNA levels were low in the daytime and high at night in wild-type mice (Fig.…”
Section: Effect Of Apoaiv Deficiency On Diurnal Variations In Plasmasupporting
confidence: 86%
“…Another feature of apoAIV that is pertinent to lipid absorption is its circadian expression (13,38,39). Serum apoAIV exhibits circadian rhythms.…”
mentioning
confidence: 99%
“…Here we show that MTP and apoB show diurnal variations. Shen et al (60) have reported that apoAIV protein and mRNA levels were high in the dark compared with those present in the day. Thus, it appears that at least three genes involved in lipoprotein assembly and secretion are coordinately regulated, and we propose that lipoprotein assembly and secretion exhibit circadian variations in the liver and intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors did not mention APOA2 as a potential candidate gene in explaining such results, the APOA2 gene is in this locus. Despite the scarcity of previous data supporting a role of APOA2 in regulating food intake, copious experimental evidence demonstrates a pivotal role of another apolipoprotein, APOA4, as a satiety signal (20,21,39,40 ). Fujimoto et al (39 ) were the first to report that APOA4 is (16,18 ).…”
Section: Discussionmentioning
confidence: 99%